Physiological responses to urban design during bicycling: A naturalistic investigation. (January 2020) - Rybarczyk, Greg; Ozbil, Ayse; Andresen, Erik; Hayes, Zachary
Highlights: Minimal research has linked bicycling comfort to micro-scale urban design metrics. Bicyclist physiology was obtained from a naturalistic investigation and GIS. Elevated and reduced bicyclist comfortability were spatially autocorrelated. Open urban spaces with no clear pathways decreased bicycling comfortability. Highly integrated urban spaces increased bicycling comfortability. Abstract: The current research set out to measure the moderating effect that urban design may have on bicyclist physiology while in transition. Focusing on the hilly City of Wuppertal, Germany, we harnessed bicyclists with mobile sensors to measure their responses to urban design metrics obtained from space syntax, while also adjusting for known traffic, terrain, and contextual factors. The empirical strategy consisted of exploratory data analysis (EDA), ordinary least squares (OLS), and a local regression model to account for spatial autocorrelation. The latter model was robust ( R 2 = 68%), and showed that two statistically significant ( p < 0.05) urban design factors influenced bicyclist physiology. Controllability, a measure of how spatially dominated a space is, increased bicyclist responses (i.e., decreased comfortability); while integration, which is related to accessibility and connectivity, had the opposite effect. Other noteworthy covariates included one-way streets and density of parked automobiles: these exerted a negative influence on bicyclist physiology. The results of this research ultimately showed that nuanced urban designs have a moderate influence on bicycling comfort. These outcomes could be utilized by practitioners focused on implementing appropriate interventions to increase bicyclist comfort levels and this mode share.